Design of a Stand-Alone Photovoltaic Model for Home Lightings and Clean Environment - Ani, Vincent Anayochukwu (Frontiers in Energy Research, 2016)
This paper gives a well-documented health risks of fuel-based lighting (kerosene lamps and fuel-powered generators) and proposed a design of a stand-alone solar PV system for sustainable home lightings in rural Nigerian area. The design was done in three different patterns of electricity consumptions with energy efficient lightings (EELs) using two different battery types (Rolls Surrette 6CS25PS and hoppecke 10 OpzS 1000) on; i) judicious power consumption, ii) normal power consumption, iii) excess power consumption; and compared them with the incandescent light bulb consumption. The stand-alone photovoltaic energy systems were designed to match the rural Nigerian sunlight and weather conditions to meet the required lightings of the household. The objective function and constraints for the design models were formulated and optimization procedure were used to demonstrate the best solution (reliability at the lowest lifecycle cost). Initial capital costs as well as annualized costs over 5, 10, 15, 20, and 25 years were quantified and documented. The design identified the most cost-effective and reliable solar and battery array among the patterns of electricity consumption with energy efficient lighting options (judicious power consumption, normal power consumption, and excess power consumption).